Migrating bullet from thorax to retroperitoneum - Ozyurtkan, Mehmet Oguzhan; Dagli, Mustafa Necati (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2016)
Bullet injuries to the thorax are observed frequently. When the radiographic location of the bullet does not correlate with the expected trajectory, a possible bullet embolism should be considered. In this article, we present a 39-year-old male patient who suffered a gunshot to his back. Patient's hemopneumothorax was treated with tube thoracostomy; however, the bullet was found to have migrated to the retroperitoneum without an overt mediastinal, diaphragmatic, or abdominal visceral organ injury. Angiography demonstrated no vascular embolism. The exact mechanism for the bullet to reach to the retroperitoneum was unknown, but a possible presence of a Bochdalek's triangle was suspected.
Keywords: Foreign body migration; penetrating injury; retroperitoneal space